MODEL PENUMBUHAN WIRAUSAHA BARU BERBASIS TECHNOPRENEURSHIP DI INKUBATOR BISNIS PSP-KUMKM LPPM UNS - R. Kunto Adi R. Kunto Adi; Erlyna Wida Riptanti; Heru Irianto (UII, 2018)
The New Technoprenership-based Entrepreneurship Growth Model is based on the activities of IbPTK New Technoprenership-Based Entrepreneurship Growth in PSP-KUMKM LPPM UNS, conducted in 2015-2017 on Business Incubator activities unit in mentoring UMKM New Entrepreneurs in Cooperation Study Center and UMKM (PSP KUMKM) LPPM UNS. The general objective of IbPTK activities is to improve the capacity building of UMMM Entrepreneurship New activities in PSP-KUMKM and SME tenant, so as to increase students and alumni in technoprenership based entrepreneurship. Specific objectives are 1) Establish a productive business unit in PSP-KUMKM based on market prospect, local potential and technological ease, 2) Stabilize the management of productive business unit, in the first year, 3). Developing productive business units in PSP-KUMKM that have been established in the first year, 4) Conducting recruitment process and selection of SME tenant candidates from UNS students or alumni, 5) Improving skills and knowledge tenant in productive business sector, in second year, 6). Conducting the incubation process to tenant who passed the selection in the second year, 7) Growing new entrepreneur-based technology, 8). Improve production capability and marketing network of tenant products, and 9). Develop a model of entrepreneurship-based technopreneurship development on campus, in the third year, as well as an outcome for three years of IbPTK activities.Problems faced by tenant partners, namely 1) The need to increase the Capacity building of mentoring activities for SMEs tenant, 2) Motivation and commitment of students or alumni in entrepreneurship based on technoprenership still need to be improved, 3) Student assistance or alumni in entrepreneurship is relatively low. Based on the above problems, the solutions and methods of the approaches offered, in general, the methods used in the implementation of this activity is the development of productive business units, observation methods, discussion, recruitment, practice, technical guidance / training and productive business assistance. In Year One (2015) implemented 1) Establishment of productive business units in PSP-KUMKM, 2) Management consolidation on productive business units, 3) The establishment of business partnerships with relevant stakeholders. The second year (2016) implemented activities: 1) Development of productive business unit in first year of PSP-KUMKM, 2) Recruitment and selection of students or alumni of UNS to become tenant, 3) Tenant apprenticeship process on productive business unit PSP-KUMKM, 4) business plan. In the third year (2017), the activities were carried out: 1) Tenant incubation process on productive unit of PSP-KUMKM, 2) Development of productive unit of PSP-KUMKM better than the second year, 3) Preparation of entrepreneurship based technopreneurship development model on campus.The outcomes achieved by the IbPTK program for three years are: 1) Development of one productive business unit in PSP-KUMKM, 2) Organizing incubation process in accordance with need assessment, 3) Tenant apprenticeship execution, 4) Tenant graduating program 5 people, 5 ) Obtaining product licensing, 6) Productive business assistance in PSP-KUMKM, 7) Campus technopreneurship development model, and 8). Publication of one scientific article in national journal with ISSN.